Thymic mucoepidermoid carcinoma: A case report - Temiz, Göktan; Yıldız, Özgür Ömer; Gülyüz, Ömer Cenap; Karaoğlanoğlu, Nurettin (Journal of Surgery and Medicine, 2019)
Mucoepidermoid carcinoma of the thymus is a rare malignant neoplasm of the anterior mediastinum. There are less than 30 cases described in the English literature. We report a case of a 77-year- old man with right chest pain. Thorax-CT scan showed a lobulated cystic mass having a focal solid portion with direct invasion of the adjacent pericardium in the anterior mediastinum. He underwent surgical resection for his anterior mediastinal mass via right thoracoscopic surgery without any complication. He had an uneventful recovery and was discharged on the sixth postoperative day.